Effect of Personal Values Similarity on B2B Relationship Value - Thayane Manosso; Juliano Silva; Verner Antoni; Claudio Damacena (BBR: Brazilian Business Review)
Similarity of values influences the relationship between companies. However, even if organizational decisions are made by people, the role played by similarity of personal values for those involved in the trade is little explored in the B2B context. Based on the similarity-attraction theory, we developed a model that explores the effect that similar of personal values between buyer and seller has in the B2B relationship value. Using a sample composed of 25 sellers and 317 buyers, we tested the hypotheses by means of polynomial regression with a response surface analysis. The results demonstrate that similarity of personal values, in regards to a social focus, between seller and buyer has a positive effect on the B2B relationship value. However, when individuals are more similar relation to personal values, the lower value the buyer perceives in the relationship with his provider. The paper also addresses implications for the theory, and B2B management theory. Relationship Implications.